COMPARATIVE EFFECTIVENESS OF AMLODIPIN MONOTHERAPY AT ADVANCED IN YEARS PATIENTS WITH ARTERIAL HYPERTENSION OF DIFFERENT DEGREES IN OUT-PATIENT STAGE - Anufrieva, L.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Forty six patients with arterial hypertension (AH) I-III stages were investigated in out-patient department. Estimated parameters were levels of systolic and diastolic blood pressures (SBP, DBP), heart rate, general index of quality of life (GIQL) and parameters of heart rate variability (total power (TP) and low- and high-frequency ratio (LF/HF)). Patients were evaluated before treatment, during the therapy and in acute pharmacological test with amlodipin. It was shown that all patients had signifficant increase of GIQL and decrease of TP. Effective decrease of SBP and DBP was found in patients with mild and moderate AH. Patients with severe AH had only depressed DBP. During the dynamic observation it was defined the decrease of total power in all patients’ groups and various LF/HF fluctuations.